Liberation from a Leisure Time (About the Thesis of Juozapas Paškauskas „Leisure Culture in Lithuania’s Major Cities and in Provincial Areas in the Late 19th – Early 20th Centuries“) - Šipelytė, Monika (Lietuvos istorijos studijos, 2018)
...